2014
DOI: 10.1093/ejo/cju081
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic miniscrews: an experimental campaign on primary stability and bone properties

Abstract: Bone characteristics play the major role in miniscrews primary stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
0
19
0
2
Order By: Relevance
“…According to the study of Holmgren et al, when a lateral load is applied on a dental implant, the force is concentrated on the top of the screw and distributed to the bone [17]. Holmgren et al also reported a positive correlation between the cortical bone thickness and the breakout force [18]. The insertion sites of the micro-screws feature relatively thick cortical as it forms the bony base which explains the resistance of the microscrews.…”
Section: Commentsmentioning
confidence: 99%
“…According to the study of Holmgren et al, when a lateral load is applied on a dental implant, the force is concentrated on the top of the screw and distributed to the bone [17]. Holmgren et al also reported a positive correlation between the cortical bone thickness and the breakout force [18]. The insertion sites of the micro-screws feature relatively thick cortical as it forms the bony base which explains the resistance of the microscrews.…”
Section: Commentsmentioning
confidence: 99%
“…There is a recommended length of >8 mm at the maxilla and 6 mm at the mandible 42 ; regardless of the NEW PARAMETERS FOR IMPROVED STABILITY OVER TIME New perspectives on miniscrews: improving stability 48 . The bone-related criteria play an important role in the short-term success rate 30,31,51 . The literature rarely differentiates between the density of the spongy bone and the thickness of the cortex, which are two different elements.…”
Section: Doi: 101051/odfen/2016020mentioning
confidence: 99%
“…Temporary Anchorage Devices (TADs), and cantilevers with a Ttitanium Molybdenum Alloy (TMA) sectional represent alternative methods for anchoring the system: a TAD is a mini screw temporarily xed to the bone for the purpose of enhancing orthodontic movement, either by supporting the reactive unit (indirect anchorage) or by obviating the need for it (direct anchorage), and is subsequently removed after use [2]. A number of clinical studies and reviews have investigated the stability of TADs for acting as stable anchor units [5][6][7][8]. In a recent study investigating anchorage loss when using a conventional TPA in comparison to a mini-screw implant, minimal mesial movement of the maxillary rst molars was observed when mini-screw implants were placed and passively engaged prior to leveling and aligning.…”
Section: Introductionmentioning
confidence: 99%